The Training Needs of French language teachers in Light of integration technology in Teaching - A Field Study in the Public Secondary Schools in Lattakia City - ونوس, ميس; هيام زريقي ,; مهند مبيض , (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to reveal the training needs and training needs of French language teachers in light of the integration of technology in Teaching in secondary schools in Lattakia city from their point of view,and know the differences in their estimates of training needs in the light of the integration of technology according to variables (scientific and educational qualification, the number of years of teaching experience, training courses in the field of integrating technology in Teaching), and to achieve the objectives of the research adopted the researcher descriptive approach, and used a questionnaire consisting of (40) phrases, applied to the research sample of French language teachers in public secondary education schools in Lattakia city which numbered (132) teachers. The results of the research showed that the training needs of French language teachers in light of the integration of technology in Teaching in secondary schools in Lattakia city were high, and the results showed that there were statistically significant differences in the estimates of French language teachers for their training needs in light of the integration of technology in Teaching attributed to the variable of scientific and educational qualification in favor of holders of the educational qualification diploma, and according to the variable of training courses in the field of integrating technology in Teaching, in favor of teachers who enrolled in training courses, while the differences were not substantial and significant according to the variable of teaching experience. The research made many recommendations, the most important of which are: increasing the awareness of French language teachers of the importance of integrating technology into education, and conducting training courses to suit the needs of French language teachers.